A novel stability-indicating method for known and unknown impurities profiling for diltiazem hydrochloride pharmaceutical dosage form (tablets) - Nitin Mahajan; Suparna Deshmukh; Mazahar Farooqui (SpringerOpen, 2021)
Abstract Background A novel gradient, high-sensitive and specific stability-indicating reverse-phase HPLC method was developed and validated for quantitative purpose of known, unknown and degradant impurities profiling for diltiazem hydrochloride tablets. The impurities were separated on the Zorbax RX C8 column (150 mm × 4.6 mm, 5 μm) with mobile phase-A consisting of a mixture of 0.05 M sodium dihydrogen phosphate monohydrate buffer pH 3.0 and methanol in the ratio 800:200v/v and mobile phase-B consisting of acetonitrile with a flow rate of 1.0 mL min−1. The column compartment was maintained at 35 °C, and the detection wavelength was 240 nm. Diltiazem hydrochloride, its known impurities and unknown impurities have been well resolved from each other. Results The linearity of the method has been demonstrated across the concentration range of 0.18 to 5.65 µg mL−1 for EP impurity-F with correlation coefficient R 2 greater than 0.99. Recovery of method was proved from LOQ to 150% for known and unknown impurities with respect to test concentration and found in between 80 and 120%. Forced degradation study and specificity experiment results with mass balance proved the stability-indicating nature of the method and separated all known, unknown impurities and degradants from each other as well as from main drug component (diltiazem hydrochloride). The mass balance for stress study was found in between 95 and 105%. Conclusion Newly developed analytical method was validated as per ICH Q2 (R1) guidelines "Validation of analytical procedure" and found linear, accurate, specific, robust and precise in the established working range.